(A)a(a-2) = 0 Is this the right simplification for statement 1:-
a = 0 or a =2
b/c = ((a+b)^2 - (a+b)^2)/(a+b)^2
I got only 1 value for a i.e. a=2
a square = 2a
a * a = 2a
a = 2
if its not correct simplification please explain, why?
Yes, that's not correct.Never reduce an equation by a variable (or expression with a variable), if you are not certain that the variable (or the expression with a variable) doesn't equal to zero. We can not divide by zero.
So, if you divide (reduce) a^2=a
you assume, with no ground for it, that a
does not equal to zero thus exclude a possible solution (notice that both a=2
satisfy the equation).
Hope it's clear.